The Influence of Promotion and Brand Image on the Purchase Decision of Samsung Handphone Goods at Universitas Efarina Pematang Siantar - Hendri Mayanta Tarigan; Andrian K Tarigan; Jopinus Saragih (International Journal of Economics (IJEC), 2022)
Study this aim for know influence promotion , Brand Image, against decision sale Samsung mobile phones throughout student user Samsung cell phone at efarina university embankment siantar . Population in study This is whole student Samsung cellphone users at Efarina University embankment cyantar with sample inside study This were 34 respondents . Retrieval technique sample is technique nonprobabilities sampling that is incidental sampling. Data collection techniques used is questionnaire. Method data analysis using technique analysis multiple linear regression, test assumption classic, test hypothesis F, test hypothesis T, coefficient determination. Research results show that, promotion, brand image, against decision purchase Samsung mobile goods. Promotion, Brand Image in a manner Partial influential positive to decision purchase Samsung mobile goods.